Mitigasi Risiko Pembiayaan Terhadap Masyarakat Prasejahtera Pada Bank BTPN Syariah - Noviendri Djalil; Andreas Rafael; Bahrul Rohman; Iswandi Iswandi; Wawan Santoso; Arief Safari; Ahmad Fakih Ijtihadi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
One of the essence of national development as stated in the fourth paragraph of the 1945 Constitution of The Republic of Indonesia Preamble is to create community welfare. To achieve this, the Bank Tabungan Pensiun Nasional Syariah (BTPNS) launched a financing product for people who are in the underprivileged category and generally have not been touched by banking services using sharia principles. Funding is given specifically to women who in fact have small businesses and have a business group of at least 5 people (groups). The distribution of this financing is definitely faced with various risks, such as financing risks and others. This study aims to determine the risk mitigation that must be carried out by Bank BTPN Syariah for financing provided to underprivileged people, so that these risks can be minimized. This research is a descriptive analysis study to see credit risk mitigation efforts conducted by Bank BTPN Syariah in order to minimize financing problem (Non Performing Financing) at the bank. Risk mitigation carried out by Bank BTPN Syariah to avoid financing problems by performing the procedure of giving financing which is tight, neat and structured and implementing 4 (four) pillars that are mutually sustainable in shaping the key character of customers consisting of brave attempted, discipline, hard work, and help each other.